PENENTUAN LAHAN PERTANIAN PANGAN BERKELANJUTAN (LP2B) KOMODITI PADI SAWAH DI KABUPATEN DHARMASRAYA - Yuchi Elchika Putri; ahyuni .; endah Purwaningsih (JURNAL BUANA, 2017)
This research have purpose to got information and about 1) Determination of Agricultural Land Sustainable Food (ALSF) at Dharmasraya .2) Distribution land of Determination of Agricultural Land Sustainable Food (ALSF) at Dharmasraya. This research is quantitatif descriptive approach, sampling technique is done by total sampling. By making the whole area in the Dharmasraya regency as samples. The data which used is secondary data obained from related institutions in this research is using methode of overlay and logic Boolean. The results of this research Determination of Agricultural Land Sustainable Food (ALSF) at Dharmasraya indicated that the land which can be recommended area potential land for agricultural landuse is type of wetlands in Dharmasraya regency is the land which has a (number) deemed for land characteristics that a total of 10 types of characteristics. The criteria of land characteristics is land with few rough material, the rocks in surface few till medium, rainfall (Q) which 0<Q<60, good drainage, the small level of erosion, the level of inundation: none, small, medium, and heavely, diverse organic content, the dept of soil is quite middle and deep, the soil acidity quite acid to quite alkhalis (5,6-8,5 Ph), slope <8, and both rock a well. Determination of Agricultural Land Sustainable Food (ALSF) at Dharmasraya regency also supported by basic infrastructure such as land located in the area of technical irrigation. Distribution land of Determination of Agricultural Land Sustainable Food (ALSF) at Dharmasraya regency with a total area of 4.123 hectares. Spread on the several subdistrict at Dharmasraya regency area of such as Timpeh subdistrict area of 1.717 Ha, Pulau Punjung subdistrict area of 760 Ha, Koto Salak subdistrict area of 36 Ha, Sitiung subdistrict area of 749 Ha, and Koto Baru subdistrict area of 861 Ha.